Evaluation of amotosalen and UVA pathogen‐reduced apheresis platelets after 7‐day storage. Issue 8 (9th July 2022) - Cancelas, Jose A.; Genthe, Jamie R.; Stolla, Moritz; Rugg, Neeta; Bailey, S. Lawrence; Nestheide, Shawnagay; Shaz, Beth; Mack, Samantha; Schroeder, Kadi; Anani, Waseem; Szczepiorkowski, Zbigniew M.; Dumont, Larry J.; et al.
Abstract: Background: Amotosalen/UVA pathogen‐reduced platelet components (PRPCs) with storage up to 7 days are standard of care in France, Switzerland, and Austria. PRPCs provide effective hemostasis with reduced risk of transfusion‐transmitted infections and transfusion‐associated graft versus host disease, reduced wastage and improved availability compared with 5‐day‐stored PCs. This study evaluated the potency of 7‐day PRPCs by in vitro characterization and in vivo pharmacokinetic analysis of autologous PCs. Study Design and Methods: The in vitro characteristics of 7‐day‐stored apheresis PRPCs suspended in 100% plasma or 65% platelet additive solution (PAS‐3)/35% plasma, thrombin generation, and in vivo radiolabeled post‐transfusion recovery and survival of 7‐day‐stored PRPCs suspended in 100% plasma were compared with either 7‐day‐stored or fresh autologous conventional platelets. Results: PRPCs after 7 days of storage maintained pH, platelet dose, in vitro physiologic characteristics, and thrombin generation when compared to conventional 7‐day PCs. In vivo, the mean post‐transfusion survival was 151.4 ± 20.1 h for 7‐day PRPCs in 100% plasma (Test) versus 209.6 ± 13.9 h for the fresh autologous platelets (Control), (T‐ΔC: 72.3 ± 8.8%: 95% confidence interval [CI]: 68.5, 76.1) and mean 24‐h post‐transfusion recovery 37.6 ± 8.4% for Test versus 56.8 ± 9.2% for Control (T‐ΔC: 66.2 ± 11.2%; 95% CI: 61.3, 71.1). Discussion: PRPCs collected in both 100% plasma as well as 65% PAS‐3/35% plasma and stored for 7 days retained in vitro physiologic characteristics. PRPCs stored in 100% plasma for 7 days retained in vivo survival. Lower in vivo post‐radiolabeled autologous platelet recovery is consistent with reported reduced count increments for allogenic transfusion.